Besiktas Aircraft Factory (1936-1943) - Yusufoglu, Nedime Tuba; Kara Pilehvarian, Nuran (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
Aircraft as a novel and exciting technological invention of the 20th century and aviation industry engendered new building types, first for the military and then for civil purposes. This developing field was pursued by the Ottoman State in the same years as the western countries and later by the Republic of Turkey, with its own facilities, and initiatives were started in this regard. Upon the emergence of military aviation, establishment of aviation organizations, and comprehension of their important role in wars and intergovernmental relationships, the Ottoman State attempted to establish a military aviation organization within its own body as of 1909 and earned itself a place in world aviation in the same period as did the United States, France, Britain, Germany, Italy, Austria and Russia (which established theirs between 1909-1912). In this context, the new emergent structure types have been hangars, airports, aviation schools, aircraft factories, and wind tunnels. Ottoman State aimed at establishing schools and educating more students in the country rather than sending two or three students abroad. To this end, as the structures of aviation Yesilkoy (San Stefano) Aviation School/Station (1912-1919), and Yesilkoy (San Stefano) Naval Aircraft School (1914-1919) were built during the inter-war period. After the Republic of Turkey was established, the facilities inherited from Ottoman State have been used and improved. Additionally, new structures have been constructed in new places. The facility of Besiktas Aircraft Factory as one of the first civil initiatives in aviation industry of the Republic of Turkey will be reviewed in this study based on the archives and architectural interpretations.
Keywords: Besiktas Aircraft Factory; aviation architecture; Nuri Demirag; aircraft; Architecture